Home Care Technology Through an Ability Expectation Lens - Wolbring, Gregor; Lashewicz, Bonnie (JMIR Publications, 2014)
Home care is on the rise, and its delivery is increasingly reliant on an expanding variety of health technologies ranging from computers to telephone "health apps" to social robots. These technologies are most often predicated on expectations that people in their homes (1) can actively interact with these technologies and (2) are willing to submit to the action of the technology in their home. Our purpose is to use an "ability expectations" lens to bring together, and provide some synthesis of, the types of utility and disadvantages that can arise for people with disabilities in relation to home care technology development and use. We searched the academic databases Scopus, Web of Science, EBSCO ALL, IEEE Xplore, and Compendex to collect articles that had the term "home care technology" in the abstract or as a topic (in the case of Web of Science). We also used our background knowledge and related academic literature pertaining to self-diagnosis, health monitoring, companionship, health information gathering, and care. We examined background articles and articles collected through our home care technology search in terms of ability expectations assumed in the presentation of home care technologies, or discussed in relation to home care technologies. While advances in health care support are made possible through emerging technologies, we urge critical examination of such technologies in terms of implications for the rights and dignity of people with diverse abilities. Specifically, we see potential for technologies to result in new forms of exclusion and powerlessness. Ableism influences choices made by funders, policy makers, and the public in the development and use of home health technologies and impacts how people with disabilities are served and how useful health support technologies will be for them. We urge continued critical examination of technology development and use according to ability expectations, and we recommend increasing incorporation of participatory design processes to counteract potential for health support technology to render people with disabilities technologically excluded and powerless.